Project-Based Digital Entrepreneurship Learning: Its Impact on Students’ Adaptability and Opportunity Recognition - Suranto Suranto; Dhany Efita Sari; Surya Jatmika; Yani Sukriah Siregar; Cahyaning Dyah Asari; Azarin Carissa Putri Laksmi; Suranto Suranto; Dhany Efita Sari; Surya Jatmika; Yani Sukriah Siregar; Cahyaning Dyah Asari (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The rapid growth of the digital economy and e-commerce platforms has opened up significant opportunities for students to engage in digital entrepreneurship. However, many students still lack the adaptability and opportunity recognition needed to respond to the ever-changing dynamics of the digital market. This study aims to analyze the effectiveness of online entrepreneurship learning experiential learning through the use of e-commerce platforms to increase adaptability and opportunity recognition students. This research uses a descriptive approach mixed methods with design project-based action research involving 50 students from the Accounting Education Study Program who were taking the Entrepreneurship Practice course. Quantitative data were collected through measurement pre-test and post-test using the Career Adapt-Abilities Scale (CAAS) and Entrepreneurial Alertness Scale (EAS) instruments, while qualitative data were obtained through interviews and observations. The results of the study showed a significant increase in scores adaptability students from 3.59 to 4.10 and the score opportunity recognition from 3.43 to 4.21. Statistical analysis using paired sample t-test the results showed that the increase was statistically significant (p < 0.001). Qualitative findings also indicated that students became more responsive to market trends, more confident in managing digital businesses, and better able to identify and evaluate business opportunities. The results of this study indicate that the integration of e-commerce-based business practices into entrepreneurship learning is effective in strengthening students' entrepreneurial competencies and professional readiness in the digital economy era.